Omega-6 oxylipins generated by soluble epoxide hydrolase are associated with knee osteoarthritis - Valdes, Ana M.; Ravipati, Srinivasarao; Pousinis, Petros; Menni, Cristina; Mangino, Massimo; Abhishek, Abhishek; Chapman, Victoria; Barrett, David A.; Doherty, Michael (American Society for Biochemistry and Molecular Biology, 2018)
Omega-6 fatty acids are important inflammatory mediators increased in joints with osteoarthritis (OA) joints. To investigate the relationship between omega-6 fatty acids and knee OA 22 omega-6 lipids (arachidonic acid, linoleic acid and 20 oxylipins) were measured using liquid chromatography-mass-spectrometry in synovial fluid from 112 knees of 102 individuals (knee OA n=58; controls n=44). Thsese were tested for association with presence of knee OA adjusting for covariates and NSAID use. Validation was performed in samples from 10 individuals with unilateral knee OA comparing affected to unaffected knees. Synovial fluid levels of three omega-6 oxylipins were associated with OA after adjusting for multiple comparisons: prostaglandin D2( PGD2), 11,12-dihydroxyeicosatrienoic acid (11,12-DHET) and 14,15-dihydroxyeicosatrienoic acid (14,15-DHET). Of these, 11,12-DHET and 14,15-DHET were also higher in affected vs unaffected knees from people with unilateral knee OA (p<0.014 and p<0.003 respectively). Levels of these compounds and of 8,9-DHET were also associated with radiographic progression (change in tibiofemoral X-ray grade over 3.3 years in 87 individuals). Circulating levels of all three were associated with gene variants at the soluble epoxide hydrolase enzyme. In conclusion, lipidomic profiling in synovial fluid identifies an additional inflammatory pathway in synovial fluid associated with knee OA and radiographic progression.